Symmetries of a center singularity of a plane vector fields - Maksymenko, S.I. (Нелінійні коливання, 2009)
Let D² ⊂ R² be a closed unit 2-disk centered at the origin O ∈ R², and F be a smooth vector field such that O is a unique singular point of F and all other orbits of F are simple closed curves wrapping once around O. Thus topologically O is a „center” singularity. Let D⁺(F) be the group of all diffeomorphisms of D² which preserve orientation and orbits of F. Recently the author described the homotopy type of D⁺(F) under the assumption that the 1-jet j¹ F(O) of F at O is non-degenerate. In this paper degenerate case j¹ F(O) is considered. Under additional ” nondegeneracy assumptions” on F the path components of D⁺(F) with respect to distinct weak topologies are described. These conditions imply that for each h ∈ D⁺(F) its path component in D⁺(F) is uniquely determined by the 1-jet of h at O. Нехай D² ⊂ R² — замкнений одиничний двовимiрний диск з центром у початку координат
O ∈ R² та F — гладке векторне поле таке, що O є єдиною особливою точкою F, а всi iншi орбiти — простими замкненими кривими, що огортають O один раз. Таким чином, топологiчно
O є особливiстю типу центр. Нехай D⁺(F) — група всiх дифеоморфiзмiв D², що зберiгають
орiєнтацiю та орбiти поля F.
Нещодавно автором було описано гомотопiчний тип D⁺(F) за умови, що 1-струмiнь j¹F(O)
поля F в O є невиродженим. У цiй статтi розглядається вироджений випадок j¹F(O). За додаткової умови невиродженостi на F описано компоненти лiнiйної зв’язностi простору D⁺(F)
вiдносно рiзних слабких топологiй. З цих умов випливає, що для кожного h ∈ D⁺(F) його компонента лiнiйної зв’язностi в D⁺(F) єдиним чином визначається 1-струменем h в O.